Gender Match and the Gender Gap in Venture Capital Financing: Evidence from Shark Tank - Michael Jetter; Kieran Stockley (Institute of Labor Economics (IZA), 2021)
Although the gender gap in entrepreneurs' success rates to secure funding is staggering, we know little about its causes. This is because observing both sides of investor-entrepreneur interactions (especially for unsuccessful pitches) is difficult in reality, and the associated extraordinary stakes complicate appropriate simulations in the laboratory. Using comprehensive data of 4,893 interactions from the popular US television show Shark Tank, we test whether gender match with entrepreneurs can explain investors' likelihood to extend funding offers. We find female investors are 30% more likely to engage with female (rather than male) entrepreneurs, while no systematic gender preferences emerge for male investors. This result is exclusive to entrepreneurs in non-male-dominated product categories but disappears in male-dominated products. Estimates are robust to the inclusion of a comprehensive set of control variables (such as asking valuation, investor-, and season-fixed effects) and a range of alternative specifications. These findings from a field setting with large, real-life stakes provide empirical support for the industry representation hypothesis regarding the gender gap in venture capital funding. While results should be interpreted with caution, our findings suggest increased numbers of women in key venture capital positions could facilitate access to funds for female entrepreneurs. Nevertheless, our setting is not suited to fully explore associated efficiency considerations.
Keywords: D91; G11; G24; G41; J16; 330; gender interaction effects; gender differences; venture capital financing; field data; high stakes bargaining